2005
DOI: 10.1080/09553000500515368
|View full text |Cite
|
Sign up to set email alerts
|

Infrared microspectroscopy study of γ-irradiated and H2O2-treated human cells

Abstract: As we previously demonstrated in radiation-induced apoptosis studies, these results show that FT-IRM, in correlation with other cellular biology techniques, might be useful for assessing immediate radiation- and oxidative-induced damage to nucleic acids and proteins in single human cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 48 publications
8
33
2
Order By: Relevance
“…In this work, the protein content and the antioxidant enzyme level were modulated differently in each mutant which agrees with those of Gault et al (2005) who indicated that, in vitro, MnSOD activity was induced after irradiation in the majority of cellular models.…”
Section: Oxidative Stresssupporting
confidence: 90%
“…In this work, the protein content and the antioxidant enzyme level were modulated differently in each mutant which agrees with those of Gault et al (2005) who indicated that, in vitro, MnSOD activity was induced after irradiation in the majority of cellular models.…”
Section: Oxidative Stresssupporting
confidence: 90%
“…In addition, the spectra revealed that irradiation induced the presence of a doublet of two spectral bands in the 1465 cm Ϫ1 region, characteristic of functional group vibrations (-CH 2 ) in lipids, and chemically shifted with regard to the control spectra ( Figure 2C). Further, irradiation caused chemical shifts in nucleic acid spectral regions, pertaining to functional group vibrations Infrared spectroscopy on MRT-irradiated mouse tumours 83 cm Ϫ1 ), which were attributed to conformational changes in membrane lipids as a result of irradiation (Gault et al 2005, Meade et al 2010. We observed two bands at ~ 1470 cm Ϫ1 and 1463 cm Ϫ1 in the untransformed absorbance spectra of irradiated mouse tumours ( Figure 2C).…”
Section: Resultsmentioning
confidence: 73%
“…FTIR has been used to detect ionising radiation-induced biochemical changes in Deinococcus radiodurans bacteria (Melin et al 2001), human keratinocyte (HaCaT) cells (Gault et al 2005, Meade et al 2010, and human lymphocytes (Gault and Lefaix 2003). To our knowledge, this is the fi rst synchrotron FTIR study to examine the response of tumour tissue to MRT at a chemical level, thus providing novel information on potential eff ects of MRT and BB on proteins, lipids and nucleic acids within the tumour.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies with bacteria have investigated the effects of γ-radiation on Deinococcus radiodurans [56], Kocuria rosea [57]and Micrococcus luteus [58] with FTIR spectroscopy. Recently Gault et al have demonstrated the sensitivity of FTIR spectroscopy to apoptotic effects in γ-irradiated lymphocytes [59] and to molecular changes in HaCaT cells exposed to both γ-radiation and hydrogen peroxide [60], together with its sensitivity to biochemical alterations in HaCaT cells irradiated with α-particles delivered by micro-beams [61]. These studies represent proof of the detection of biochemical effects in irradiated biological species with spectroscopic methods.…”
Section: Introductionmentioning
confidence: 95%